Living in windy environments: new insights on mechanisms supporting the invasion success of alien plant species at the Kerguelen Islands - Renault, David; Puijalon, Sara; Barrio, Miguel; Bertrand, Mathilde; Tolosano, Matteo; Pierre, Aurélien; Ferreira, Charly; Prouteau, Clémentine; Bittebière, Anne‐kristel (HAL CCSD, 2018)
International audience